2019
DOI: 10.1186/s12199-019-0807-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of needlestick injury among healthcare workers in Ethiopia: a systematic review and meta-analysis

Abstract: Background Health facilities can provide diagnostic, curative, and prognostic services for the community. While providing services, healthcare workers can be exposed to needlestick injuries that can transmit pathogenic organisms through body fluids. Objective The aim was to establish the pooled prevalence of needlestick injuries among healthcare workers in Ethiopia. Methods This systematic review and meta-analysis was conducted according to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 56 publications
4
17
3
1
Order By: Relevance
“…Furthermore, in this meta-analysis it was observed that those workers who had drinking alcohol, smoking cigarette and chewing khat habit and having work related stress had higher work related injury as compared to their counterparts. This nding is supported by previous studies conducted so far (32,34,35). The possible explanation could be because of a worker's substance use habit and work related stress reduces his/her concentration at work and use of PPE habit during work.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, in this meta-analysis it was observed that those workers who had drinking alcohol, smoking cigarette and chewing khat habit and having work related stress had higher work related injury as compared to their counterparts. This nding is supported by previous studies conducted so far (32,34,35). The possible explanation could be because of a worker's substance use habit and work related stress reduces his/her concentration at work and use of PPE habit during work.…”
Section: Discussionsupporting
confidence: 84%
“…During the interviews, the interviewers heard anecdotal reports from several respondents that some of their colleagues could not continue their job and had resign from their job because of the worries and anxieties after experiencing NSSIs. A study suggested an association between NSSIs and depressive symptoms 31) showed that the rates of NSSI were similar or higher, but the differences were less than twice comparing to this study: West African countries (45.7%) 32) , Turkey (64.1%) 33) , Ethiopia (63.6%) 34) , Nepal (74.3%) 35) , and Thailand (55.5%) 36) (The first four papers are NSSIs for the past 6 months, and the last paper is NSSIs for the past year). The variation on the rates of NSSIs may be due to variations in scope of hospital services.…”
Section: Discussioncontrasting
confidence: 62%
“…This study found 42.1% of hospital workers experienced NSSIs over entire careers and 11.4% of them experienced in the past 6 months. Previous studies from developing countries, which reported the rate of NSSIs among hospital workers over entire careers, showed that the rates of NSSI were similar or higher, but the differences were less than twice comparing to this study: West African countries (45.7%) 31 ) , Turkey (64.1%) 32 ) , Ethiopia (63.6%) 33 ) , Nepal (74.3%) 34 ) , and Thailand (55.5%) 35 ) (The first four papers are NSSIs for the past 6 months, and the last paper is NSSIs for the past year). The variation on the rates of NSSIs may be due to variations in scope of hospital services.…”
Section: Discussioncontrasting
confidence: 57%
“…Occupational health and safety are vital in every organization, particularly in healthcare settings. 31 This study reviewed the prevalence of needle-stick injuries among healthcare workers and factors associated with the prevalence of NSIs in developing countries. In the review, a total of 13 articles that assess the prevalence of NSIs and/or factors associated with NSIs were included.…”
Section: Discussionmentioning
confidence: 99%